Associação entre sucção nutritiva e não nutritiva e maloclusão na dentição mista - Belitz, Glauber Sousa (2021)
Aim: The aim of this study was to evaluate the association between malocclusions in the mixed dentition stage, breastfeeding and past non-nutritive sucking habits in school-age children. Methods: In total 547 school children in the mixed dentition stage, in the age-range between 7 and 13 years, were evaluated, by means of questionnaires and clinical examinations. Binomial and Multinomial Logistic Regression Models were used to evaluate the association between breastfeeding, finger and pacifier sucking habits, according to the outcomes posterior cross bite, changes in overjet and overbite. Results: Individuals who had non-nutritive sucking habits had 2.16 times more chance of having anterior open bite (AOB) (OR 2,16; CI 95%, 1.07-4.33). Individuals who had non-nutritive sucking habits had 2.39 times more chance of having posterior cross bite (PCB) (OR 2.39; CI 95%, 1.56-5.49). Children who were exclusively breastfed up to six months of age had higher frequency of normality for overjet and overbite, and the lowest PCB indexes. However, in adjusted analysis, breastfeeding showed no association with the malocclusions studied, in the mixed dentition stage. Conclusion: Breastfeeding was not associated with the development of malocclusions, while past nonnutritive sucking habits were associated with the occurrence of malocclusion in mixed dentition.